2020
DOI: 10.21203/rs.3.rs-39538/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Systematic Review Assessing the Under-Representation of Elderly Adults in COVID-19 Trials

Abstract: Abstract BackgroundCoronavirus disease (COVID-19) has caused a pandemic threatening millions of people worldwide. Yet studies specifically assessing the geriatric population are scarce. We aimed to examine the participation of elderly patients in therapeutic or prophylactic trials on COVID-19.MethodsIn this review, randomized controlled trials (RCTs; n=12) comparing therapeutic or prophylactic interven… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…(Jones et al, 2021, Rudolph et al, 2021, Zaqout et al, 2021 Given the highest mortality observed in the elderly of long-term care facilities and higher exposure risk for health care workers (Team, 2020, Wu and McGoogan, 2020, Zhou et al, 2020, many countries have prioritized both high-risk groups for vaccinations (Britton et al, 2021, Lopez Bernal et al, 2021. However, elderly patients are less represented in clinical trials which mainly enrolled young population (Prendki et al, 2020). We synthesized evidence in real-world by vaccinated population.…”
Section: Discussionmentioning
confidence: 99%
“…(Jones et al, 2021, Rudolph et al, 2021, Zaqout et al, 2021 Given the highest mortality observed in the elderly of long-term care facilities and higher exposure risk for health care workers (Team, 2020, Wu and McGoogan, 2020, Zhou et al, 2020, many countries have prioritized both high-risk groups for vaccinations (Britton et al, 2021, Lopez Bernal et al, 2021. However, elderly patients are less represented in clinical trials which mainly enrolled young population (Prendki et al, 2020). We synthesized evidence in real-world by vaccinated population.…”
Section: Discussionmentioning
confidence: 99%
“…Fitbit activity monitors have been compared to PSG in outpatient settings with healthy individuals and demonstrate acceptable agreement in terms of total sleep time, sleep efficiency, 14 sensitivity (ability to detect true sleep) and accuracy (ability to detect both true sleep and true wakefulness) 15 . Although wrist activity monitors provide an alternate method to measure sleep for clinical and research and there is fair agreement in healthy populations, their ability to measure sleep in hospitalized patients with neurocognitive disorders remains untested 16 …”
Section: Introductionmentioning
confidence: 99%
“…15 Although wrist activity monitors provide an alternate method to measure sleep for clinical and research and there is fair agreement in healthy populations, their ability to measure sleep in hospitalized patients with neurocognitive disorders remains untested. 16 Our objective was to compare the consistency of activity monitors to record and measure sleep between study participants with and without neurocognitive diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…Given the clinical vulnerability of LTCF residents to COVID-19, there is considerable interest in understanding the immune correlates of vaccine protection within this group. However, older and more frail populations are often under-represented in vaccine trials, [3][4][5][6] making the extrapolation of data from registration studies directly to resident populations in LTCFs difficult. [7][8][9] Although most COVID-19 vaccine schedules comprise the administration of two doses, several countries such as the UK have adopted a policy of delaying the second dose to increase the proportion of the population vaccinated with at least one dose.…”
Section: Introductionmentioning
confidence: 99%